Various Aspects of Worship in Deuterocanonical and Cognate Literature - Balla, Ibolya; Xeravits, Géza G.; Zsengellér, József (Deuterocanonical and Cognate Literature Yearbook ;, 2017)
The volume contains papers read at the International Conference of the ISDCL, held in Budapest in 2015. The contributors explore various aspects of worship as reflected in the literature of Judaism from the Second Temple period to Late Antiquity. The volume provides a fresh reading of various crucial issues especially within Old Testament Apocrypha and Pseudepigrapha, Rabbinic literature, Gnostic traditions, and the emerging synagogue. The papers analyse texts and artefacts that reveal how various groups of Judaism understood the concept of worship-a pre-eminent form of expressing religious identity and interpreting fundamental traditions.